Animal and cellular models of Alzheimer’s disease: Progress, promise, and future approaches. - Trujillo-Estrada, Laura Isabel; Sánchez-Mejías, Elisabeth; Sánchez-Varo, Raquel María; García-León, Juan Antonio; Nuñez-Diaz, Cristina; Dávila-Cansino, José Carlos; Vitorica Ferrández, Javier; LaFerla, Frank; Moreno-González, Inés; Gutiérrez-Pérez, Antonia; Baglietto-Vargas, David; Baglietto-Vargas, David (SAGE, 2022)
Alzheimer’s disease (AD) is an incurable neurodegenerative disease affecting over 45 million people worldwide. Transgenic mouse models have made remarkable contributions toward clarifying the pathophysiological mechanisms behind the clinical manifestations of AD. However, the limited ability of these in vivo models to accurately replicate the biology of the human disease have precluded the translation of promising preclinical therapies to the clinic. In this review, we highlight several major pathogenic mechanisms of AD that were discovered using transgenic mouse models. Moreover, we discuss the shortcomings of current animal models and the need to develop reliable models for the sporadic form of the disease, which accounts for the majority of AD cases, as well as human cellular models to improve success in translating results into human treatments.
https://openpolicyfinder.jisc.ac.uk/id/publication/9526
Keywords: Alzheimer, Enfermedad de - Modelos animales; Alzheimer's disease; Animal models; Cellular models